Deteksi Mata Mengantuk pada Pengemudi Mobil Menggunakan Metode Viola Jones - Imanuddin Imanuddin; Fachrid Alhadi; Raza Oktafian; Ahmad Ihsan (Universitas Bumigora, 2019)
Computer Vision is one of the branches of Image processing science that allows a combination of human beings, such as identifying an object like an eye and taking a decision. Many of the face detection systems use the Viola Jones method as an object detection method. The method of Viola Jones is known by having high speed and accuracy because it is useful to combine several concepts such as (Haar Features, Integral Image, AdaBoost, and Cascade Classifier) into a major method for detecting objects. The programming language used in this study uses the MATLAB programming language to facilitate the process of creating the system. The research aims to implement Viola Jones into a simple eye-sensing drowsiness system by utilizing the existing libraries in the MATLAB programming language. Once the system is completed, a system test is performed against the detected drowsiness detection characteristics. This eye drowsiness detection system aims to determine if the car rider is sleepy or not when driving with an input in the form of eye detection taken using a digital camera and then inserted into a language Programming GUI Matlab where the value is taken binary eyes, sleepy eyes and not sleepy that will be a reference that will be processed later so that it can produce the output of a warning sound to the rider of the sleepy car vehicle or not The sleepy automatically. The testing of the program gained an amount detected 7 eyes of 10 eyes by using BW 0255 level which is useful to accelerate a program to detect sleepy eyes.